Implementation of Indirect Field Oriented Control Using Space Vector Pulse Width Modulation for the Control of Induction Motor - Kasula, Sabin; Shrestha, Bibek; Katwal, Karan; Dahal, Roshan (International Journal on Engineering Technology, 2023)
For the efficient speed control of three phase Induction motor, the Vector control or Field oriented control (FOC) technique is used for the Voltage source inverter. In implementing FOC the angular position of the rotor flux vector is to be determined. There are two methods (direct and indirect) of vector control for the evaluation of rotor angle. In an Indirect field-oriented control (IFOC) method rotor angle is estimated from slip frequency and rotor frequency without using a sensor (sensors are used in direct FOC) which are achieved in a synchronously rotating frame. IFOC produces high performance in induction motor drives by decoupling rotor flux and torque, so it can be separately controlled by stator direct-axis current and quadrature-axis current respectively, like in a DC motor. The rotor flux orientation method is used for incorporating PI control system using the Space Vector Pulse Width Modulation (SVPWM) technique. The Induction motor drive control generally involves three different PI controllers for torque, speed, and flux respectively. Through the simulation result, varying the load torque, and reference speed is achieved within a few milliseconds, and the behavior of the separately excited DC motor is observed.